Analyzing the Attitude of Iranian Auditing Experts toward the Business Risk Audit Efficiency for Stakeholders - Shoeyb Rostami OstadKelayeh; Mohammad Ali Aghaei; Kumars Biglar (Iranian Journal of Accounting, Auditing & Finance)
In evaluating a business based on the business risk audit (BRA) approach, auditors should define and perceive strategic management control techniques and operating processes. They should also select risk control processes in vital operating processes to estimate the type and magnitude of residual business risks that might affect the accuracy and fairness of financial statements. Given the international re-emergence of BRA concepts in recent years, this approach is considered an essential innovation in the auditing methodology. This study aims to analyze the attitude of Iranian auditing experts toward the BRA efficiency for stakeholders. For this purpose, a researcher-made questionnaire was designed in three dimensions: normative legitimacy of BRA, pragmatic legitimacy of BRA, and cognitive legitimacy of BRA (per dimensions of the legitimacy theory proposed by Greenwood, Suddaby & Hinings, 2002). The questionnaire was then distributed to a research sample including the Partners, Audit Org., and IACPA obtained at the end of 2021; the research results indicated that the BRA approach had normative legitimacy (m= 3.61), pragmatic legitimacy (m= 3.78), and cognitive legitimacy (m= 3.29) in Iran for the opinions of experts and statistical findings. Given the flaws and shortcomings of Iran’s current auditing framework, integrating the BRA approach into the current framework will be promising. At the same time, this approach can prevent over-auditing due to its proven inherent value. It can also be considered a naturally correct method of auditing.